Resin-containing silicon dioxide composition as well as preparation method and application thereof
By using a resin-containing silica composition in the encapsulation material of the coreless substrate, the porous structure of the porous silica is used to penetrate the inside and outside, and the problem of warping of the coreless substrate package is solved, and the consideration of high rigidity and low thermal expansion coefficient is achieved.
Patent Information
- Application Number
- CN202510132717.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-25
AI Technical Summary
When the coreless substrate is equipped with semiconductor components and packaged, warping problems are prone to occur. The prior art reduces the thermal expansion coefficient by increasing the filling amount of silica and toughening agent, resulting in a decrease in rigidity and impact resistance of the package.
Using a resin-containing silica composition, the resin penetrates the inside and outside through the porous structure of the porous silica, enhancing the rigidity and impact resistance of the packaging material, and limiting the expansion of the resin through the porous structure to alleviate the warping problem.
It is achieved to avoid warping problems while maintaining high rigidity and low thermal expansion coefficient, so that the coreless substrate is not easy to warp during the packaging process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor packaging technology, and in particular to a resin-containing silicon dioxide composition and a preparation method and application thereof. Background Art
[0002] Coreless substrate is a substrate without inner layer (core material). It forms a printed circuit board with the required circuit pattern and structure by laminating copper foil, insulation layer and other materials together. Coreless substrate is born in response to the demand of modern electronic products for high density, high reliability and thinness. It has the characteristics of lightness, shortness and high circuit control precision.
[0003] Since the coreless substrate is thinned by removing the support body (core substrate), the rigidity decreases. Therefore, when the semiconductor element is mounted and packaged, the problem of warping of the semiconductor package becomes more significant. Warping is considered to be one of the factors causing poor connection between the semiconductor element and the printed circuit board. For the coreless substrate, it is urgently desired to reduce the warping more effectively.
[0004] Existing studies have shown that as the thermal expansion coefficient of semiconductor packages increases, they tend to warp more. In order to reduce the thermal expansion coefficient, existing packaging materials generally increase the amount of silica and toughening agents. However, simply increasing the amount of silica and toughening agents in packaging materials will reduce the rigidity and impact resistance of the package, which will increase the warping problem and make it more difficult to maintain the adhesion between the electronic package and the substrate during transportation.
[0005] For example, in the prior art, a Chinese patent with application publication number CN113403014A discloses a bottom filler for electronic packaging devices, a preparation method and an electronic packaging device, which modifies the surface of silicon dioxide by using a polystyrene layer and a silane coupling agent, eliminates hydrogen bonds on the surface of silicon dioxide, makes the modified silicon dioxide easy to disperse, increases the filling amount of silicon dioxide to 75%~80%, and thus reduces the thermal expansion coefficient of the bottom filler for electronic packaging devices. The packaging material of patent CN113403014A has the following problems: it increases the filling amount of silicon dioxide to 75%~80%, which will lead to a decrease in the rigidity and impact resistance of the package body, and leads to a decrease in the bonding performance between the semiconductor electronic device and the package body, which will aggravate the warping problem of the coreless substrate when preparing the coreless substrate. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a resin-containing silicon dioxide composition and a preparation method and application thereof.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a resin-containing silica composition, comprising porous silica and resin, wherein the resin penetrates the inside and outside of the porous silica through the pore structure of the porous silica; based on the total weight of the composition, the weight of the porous silica accounts for 30% to 70%.
[0008] The present invention makes the following improvements to the resin-containing silica composition: first, the resin is allowed to pass through the inside and outside of the porous silica through the pore structure of the porous silica, so that the resin is continuous in the composition and the rigidity and impact resistance of the packaging material are enhanced; second, the resin is allowed to pass through the inside and outside of the porous silica through the pore structure of the porous silica, and the porous structure is used to limit the expansion of the resin in the pores, thereby alleviating the warping problem; third, based on the improvements of the first and second points above, the composition of the present invention can be added with 30-70% by weight of porous silica, and the warping problem caused by the decrease in rigidity is avoided, so that the composition of the present invention is presented with a large amount of porous silica added. Since the thermal expansion coefficient of the silica material itself is low, the composition of the present invention has a lower thermal expansion coefficient.
[0009] Preferably, the average pore size of the porous silica is 5 to 100 nm based on the BJH method.
[0010] In order to ensure that the porous silica does not cause a decrease in rigidity under the situation of a large filling amount, the present invention continues to improve the present composition. In multiple experiments on the composition, it was found that the average number of pore diameters of the porous silica is within the range of 5 to 100 nm, which can keep the thermal expansion coefficient of the resin-containing silica composition at a low level, while at the same time, the rigidity of the composition is kept at a high level.
[0011] More preferably, the average pore size of the porous silica is 16 to 60 nm based on the BJH method.
[0012] The selection of the pore size of porous silica is not independent. Taking into account the effects of reducing the coefficient of thermal expansion and improving rigidity, the inventors found that the selection of the pore size of porous silica is related to the weight proportion of the porous silica and the type of resin. Compared with the non-intersection range of 5 to 100 nm, when the average number of the pore size of porous silica is in the range of 16 to 60 nm, the rigidity of the composition can be maintained at a higher level. This further illustrates that when the average number of the pore size of porous silica is in the range of 16 to 60 nm, the above-mentioned effect of allowing the resin to pass through the porous silica through the pore structure of the porous silica, the effect of the inside and outside of the porous silica, is better displayed.
[0013] Preferably, the volume-based cumulative 50% particle size of the porous silica is 0.3-2 μm.
[0014] Preferably, based on the BET method, the specific surface area of the porous silica is 15 to 150 m 2 / g.
[0015] Preferably, the resin is selected from one or more of epoxy resin, cyanate resin, polyphenylene ether resin and hydrocarbon resin.
[0016] Preferably, when cured at 200° C. for 60 minutes, the thermal expansion coefficient of the composition in the range of 25° C. to 120° C. is 5-50 ppm / K.
[0017] In a second aspect, the present invention provides a method for preparing a resin-containing silica composition, comprising the following steps: mixing porous silica and resin so that the resin passes through the pore structure of the porous silica and penetrates the inside and outside of the porous silica; based on the total mass of the composition, the weight proportion of the porous silica is 30% to 70%.
[0018] As a preferred preparation method, the mixing comprises the following steps: preheating the porous silica to not less than 60° C., adding the resin and stirring at a speed of 1000-3000 rpm.
[0019] As a preferred preparation method, dense silica is also added during the mixing.
[0020] As a preferred embodiment of the above preparation method, the added mass of the dense silica is not higher than 20% of the total mass of the composition.
[0021] As the above preparation method, based on the BET method, the specific surface area of the dense silica is 1.5~15m 2 / g; the volume-based cumulative 50% particle size of dense silica is 0.3~2μm.
[0022] In a third aspect, the present invention provides use of the silicon dioxide composition in preparing a coreless substrate.
[0023] Compared with the prior art, the present invention has the following technical effects: The present invention makes the following improvements to the resin-containing silica composition: first, the resin is made to penetrate the inside and outside of the porous silica through the pore structure of the porous silica, so that the resin is coherent in the composition, and the rigidity and impact resistance of the packaging material are enhanced; second, the resin is made to penetrate the inside and outside of the porous silica through the pore structure of the porous silica, and the porous structure is used to limit the expansion of the resin in the hole, and the warping problem is alleviated; third, based on the improvements of the first and second points above, the composition of the present invention can add 30~70% by weight of porous silica, and avoid the warping problem caused by the decrease in rigidity, so that the composition of the present invention is presented with a large amount of porous silica added, and because the thermal expansion coefficient of the silica material itself is low, the composition of the present invention has a lower thermal expansion coefficient. After the above improvements, the resin-containing silica composition provided by the present invention has a low thermal expansion coefficient, and has high rigidity, so that the composition can remain non-warping when forming a coreless substrate. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.
[0025] The present invention provides a resin-containing silica composition, comprising porous silica and resin, wherein the resin penetrates the inside and outside of the porous silica through the pore structure of the porous silica; based on the overall weight of the composition, the weight proportion of the porous silica is 30% to 70%.
[0026] The existing substrate material reduces the thermal expansion coefficient of the package by increasing the filling amount of silica. However, increasing the filling amount of silica in the substrate material will cause the impact resistance and rigidity of the existing substrate material to be reduced, which will also cause warping problems and make it difficult to maintain the adhesion of the substrate. In this case, in order to improve the existing packaging materials, the present invention makes the following improvements to the resin-containing silica composition: first, the resin is made to pass through the inside and outside of the porous silica through the pore structure of the porous silica, so that the resin is continuous in the composition, and the rigidity and impact resistance of the packaging material are enhanced; second, the resin is made to pass through the inside and outside of the porous silica through the pore structure of the porous silica, and the porous structure is used to limit the expansion of the resin in the hole, and the warping problem is alleviated; third, based on the improvements of the first and second points above, the composition of the present invention can add 30~70% by weight of porous silica, and avoid the warping problem caused by the decrease in rigidity, so that the composition of the present invention is presented with a large amount of porous silica, and because the thermal expansion coefficient of the silica material itself is low, therefore, the composition of the present invention has a lower thermal expansion coefficient. Through the above improvements, the resin-containing silicon dioxide composition disclosed in the present invention has a low thermal expansion coefficient and high rigidity, so that the composition can remain free of warping when forming a coreless substrate.
[0027] In the resin-containing silica composition disclosed in the present invention, the pore structure of the porous silica includes through holes. The porous silica has a through-hole structure, which allows the resin to pass through the inside and outside of the porous silica through the pore structure of the porous silica. For example, the porous silica product YYW0605 from the market, which includes through holes, can be applied to the present invention to achieve the effect of the above-mentioned resin-containing silica composition.
[0028] In one embodiment, based on the BJH method, the average pore size of the porous silica is preferably 5-100 nm.
[0029] In order to ensure that the porous silica does not cause a decrease in rigidity under the situation of a large filling amount, the present invention continues to improve the present composition. In multiple experiments on the composition, it was found that the average number of pore diameters of the porous silica is within the range of 5 to 100 nm, which can keep the thermal expansion coefficient of the resin-containing silica composition at a low level, while at the same time, the rigidity of the composition is kept at a high level.
[0030] The selection of the pore size of porous silica is not independent. Comprehensively reducing the thermal expansion coefficient and improving the rigidity, the inventors found that the selection of the pore size of porous silica is related to the weight ratio of the porous silica and the type of resin. In one embodiment, based on the BJH method, the average number of the pore size of porous silica is preferably 16~60nm. It is found from this embodiment that, unexpectedly, compared to the non-intersection range of the range of 5~100nm, when the average number of the pore size of porous silica is in the range of 16~60nm, the rigidity of the composition can be maintained at a higher level. It is further illustrated that when the average number of the pore size of porous silica is in the range of 16~60nm, the above-mentioned effect of allowing the resin to pass through the inside and outside of the porous silica through the pore structure of the porous silica is better displayed.
[0031] In this embodiment, the resin is an epoxy resin and a hydrocarbon resin, which can make the effect of reducing the thermal expansion coefficient and improving the rigidity comprehensive reflect the best. It is thus explained that the effect of allowing the resin to pass through the inside and outside of the porous silica through the pore structure of the porous silica needs to be obtained by combining a variety of specific conditions, specifically: the weight proportion of the porous silica, the pore size range of the porous silica and the type of resin. The resin affects the effect of allowing the resin to pass through the inside and outside of the porous silica through the pore structure of the porous silica through its physical properties in the mixed state when preparing the composition. The physical properties of the resin in the mixed state when preparing the composition include: the hydrophilicity of the resin, the charge properties of the resin, and the fluidity and permeability of the resin. Specifically, the hydrophilicity will affect the interaction between the resin and the porous silica pore wall. If the interaction force between the resin and the silica pore wall is weak, the penetration effect of the resin may be affected; the charge property is reflected in that the resin carries a charge opposite to the silica pore wall, so the penetration of the resin will be promoted by the action of electrostatic attraction. On the contrary, if the charge is the same, electrostatic repulsion may be generated to hinder the penetration of the resin; the resin needs to flow through the pore structure of the porous silica under suitable fluidity, so that the resin is retained inside and outside the pore structure, forming an effect of penetrating the inside and outside of the porous silica, and part of the resin enters the pore structure or is discontinuous in the pore structure after entering, which is not the effect of penetrating the inside and outside of the porous silica described in the present invention. The resin is discontinuous inside and outside the pore structure, which will cause the rigidity of the composition to decrease. The resin is an epoxy resin and a hydrocarbon resin, which can make the above-mentioned physical properties best, so as to present the best effect of penetrating the inside and outside of the porous silica.
[0032] In one embodiment, the porosity of the porous silica is preferably 30-70%.
[0033] When the pore size of porous silica is within a certain range, the porosity of porous silica is 30-70%, which can improve the continuity of the resin in the composition and thus improve the rigidity of the composition. The critical point of the rigidity improvement of porous silica is mainly due to the fact that for resins with high viscosity, after a certain critical pore size, the resin can enter the pores of the particles. At this time, the optimization of porosity to improve the rigidity of the molding composition is meaningful.
[0034] In one embodiment, the volume-based cumulative 50% particle size of the porous silica is preferably 0.3-2 μm.
[0035] It can be seen that when the volume-based cumulative 50% particle size of the porous silica is 0.3-2 μm, the rigidity of the resin-containing silica composition is more excellent. The reason for this phenomenon is that within the range of the cumulative 50% particle size of 0.3-2 μm, a large filling amount of porous silica can be ensured, and the porous silica having a pore structure with a pore size of 5-100 nm can be ensured to have a certain structural thickness, so that the resin-containing silica composition can show a more excellent rigidity effect.
[0036] In one embodiment, based on the BET method, the specific surface area of the porous silica is preferably 15 to 150 m 2 / g.
[0037] The specific surface area will affect the dispersibility of the porous silica powder, and the specific surface area of the porous silica is 15-150 m 2 / g, the dispersibility of the porous silica can be improved, thereby improving the effect of the resin penetrating the inside and outside of the porous silica through the pore structure of the porous silica.
[0038] In one embodiment, the resin is selected from one or more of epoxy resin, cyanate resin, polyphenylene ether resin, and hydrocarbon resin.
[0039] When the resin is selected from epoxy resin, cyanate resin, polyphenylene ether resin, and hydrocarbon resin, the rigidity of the porous silica will not be reduced when the porous silica is filled in a large amount. This is reflected in that the thermal expansion coefficient of the resin-containing silica composition is maintained at a relatively low level, while at the same time, the rigidity of the composition is maintained at a relatively high level.
[0040] In one embodiment, when cured at 200° C. for 60 minutes, the thermal expansion coefficient of the composition in the range of 25° C. to 120° C. is 5-50 ppm / K.
[0041] According to the silica composition disclosed in the present invention, the present invention provides a method for preparing a resin-containing silica composition, comprising the following steps: mixing porous silica and resin, so that the resin passes through the pore structure of the porous silica and penetrates the inside and outside of the porous silica; based on the total mass of the composition, the weight proportion of the porous silica is 30% to 70%.
[0042] In the implementation of the above preparation method, the mixing includes the following steps: preheating the porous silica to not less than 60° C., adding the resin and stirring at a speed of 1000-3000 rpm.
[0043] The above-mentioned effect of allowing the resin to penetrate the inside and outside of the porous silica through the pore structure of the porous silica is an important technical means for forming the excellent effect of the composition of the present invention. The physical properties of the resin and the porous silica in the mixed state when preparing the composition will affect the above-mentioned effect of allowing the resin to penetrate the inside and outside of the porous silica through the pore structure of the porous silica. During mixing, preheating the porous silica will affect the penetration behavior of the resin, which is beneficial to the consistency of the inside and outside of the pore structure of the porous silica, so that the resin can penetrate the pore structure by relying on its own fluidity in the mixed state.
[0044] In the implementation of the above preparation method, dense silica is also added during the mixing.
[0045] The dense silica can be understood as non-porous silica. Generally, dense silica is a silica material with a high density and a relatively compact structure, and its surface is dense and has no pores or few pores. The dense silica can be prepared by chemical synthesis, deflagration, flame melting and other methods.
[0046] In the implementation of the above preparation method, based on the BET method, the specific surface area of the dense silica is 1.5~15m 2 / g; the volume-based cumulative 50% particle size of dense silica is 0.3~2μm.
[0047] In the implementation of the above preparation method, the added mass of the dense silica is not higher than 20% of the total mass of the composition.
[0048] According to the silicon dioxide composition and the preparation method thereof disclosed in the present invention, the present invention provides the use of the silicon dioxide composition in the preparation of a coreless substrate.
[0049] In order to make the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments. Hereinafter, Zhejiang Sanshiji New Materials Technology Co., Ltd. is abbreviated as Sanshiji.
[0050] Example 1 Preparation of a Silicon Dioxide Composition Containing Resin The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin (a product from Shanghai Huayi Resin Co., Ltd., model number SW-200, the same below) was added, and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a silica composition containing resin. Then, the composition was cured at 200°C for 60 minutes to form.
[0051] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0052] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0053] Example 2 Preparation of a Silicon Dioxide Composition Containing Resin The porous silica (a product from Sanshiki, model number YYW0305) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1000 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0054] in: Based on the total weight of the composition, the weight proportion of the porous silica is 30%, and the weight proportion of the resin is 70%.
[0055] Based on the BJH method, the average pore size of porous silica is 5 nm and the specific surface area is 150 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.3 μm; and the porosity of the porous silica was 30%.
[0056] Example 3 Preparation of a Silicon Dioxide Composition Containing Resin The porous silica (a product from Sanshiki, model number YYW1010) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 3000 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0057] in: Based on the total weight of the composition, the weight of the porous silica accounts for 70%, and the weight of the resin accounts for 30%.
[0058] Based on the BJH method, the average pore size of porous silica is 50 nm and the specific surface area is 51 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 1.0 μm; and the porosity of the porous silica was 53%.
[0059] Example 4 Preparation of a Silicon Dioxide Composition Containing Resin The porous silica (a product from Sanshiki, model number YYW2010) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0060] in: Based on the total weight of the composition, the weight proportion of the porous silica is 63%, and the weight proportion of the resin is 37%.
[0061] Based on the BJH method, the average pore size of porous silica is 100 nm and the specific surface area is 15 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 2.0 μm; and the porosity of the porous silica was 70%.
[0062] Example 5 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 12 nm. The other steps are the same as those in Example 1. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWB605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0063] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0064] Based on the BJH method, the average pore size of porous silica is 12 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0065] Example 6 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 20 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWC605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0066] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0067] Based on the BJH method, the average pore size of porous silica is 20 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0068] Example 7 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 30 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWD605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0069] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0070] Based on the BJH method, the average pore size of porous silica is 30 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0071] Example 8 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 40 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWE605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0072] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0073] Based on the BJH method, the average pore size of porous silica is 40 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0074] Example 9 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 51 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWF605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0075] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0076] Based on the BJH method, the average pore size of porous silica is 51 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0077] Example 10 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 60 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWG605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0078] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0079] Based on the BJH method, the average pore size of porous silica is 60 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 58%.
[0080] Example 11 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 72 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWH605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0081] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0082] Based on the BJH method, the average pore size of porous silica is 72 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 58%.
[0083] Example 12 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 84 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWI605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0084] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0085] Based on the BJH method, the average pore size of porous silica is 84 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 58%.
[0086] Example 13 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the average pore size of the porous silica is 100 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWJ605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a silica composition containing resin. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0087] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0088] Based on the BJH method, the average pore size of porous silica is 100 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 58%.
[0089] Example 14 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the epoxy resin is replaced by hydrocarbon resin. The other steps are the same as those in Example 1. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then hydrocarbon resin (a product from Kraton, model number 1118, the same below) was added, and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a silica composition containing resin. Then, the composition was cured at 200°C for 60 minutes to form.
[0090] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0091] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0092] Example 15 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the epoxy resin is replaced by hydrocarbon resin, and the average pore size of the porous silica is 40 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWE605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then hydrocarbon resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0093] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0094] Based on the BJH method, the average pore size of the porous silica is 40 nm, and the specific surface area is 80 m2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica is 0.6 μm; and the porosity of the porous silica is 41%.
[0095] Example 16 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the epoxy resin is replaced by hydrocarbon resin, and the average pore size of the porous silica is 84 nm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWI605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then hydrocarbon resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0096] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0097] Based on the BJH method, the average pore size of porous silica is 84 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 58%.
[0098] Example 17 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the epoxy resin is replaced by a cyanate resin. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, and then the porous silica was preheated to 60°C, and then a cyanate resin (a product from Yangzhou Tianqi, model number C01PS) was added and stirred at a speed of 1500 rpm for 1 hour to obtain a silica composition containing a resin. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0099] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0100] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0101] Example 18 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the epoxy resin is replaced by polyphenylene ether resin. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, and then the porous silica was preheated to 60°C, and then polyphenylene ether resin (a product from SABIC, model number SA9000) was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0102] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0103] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0104] Example 19 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the volume-based cumulative 50% particle size (D50) of the porous silica is 0.2 μm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0202) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0105] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0106] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.2 μm; and the porosity of the porous silica was 41%.
[0107] Example 20 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the volume-based cumulative 50% particle size (D50) of the porous silica is 3 μm. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW3010) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0108] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0109] Based on the BJH method, the average pore size of the porous silica is 16 nm, and the specific surface area is 80 m2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica is 3.0 μm; and the porosity of the porous silica is 41%.
[0110] Example 21 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the specific surface area of porous silica is 10.1m 2 / g. This embodiment is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW06M5) was heated to 60°C and kept warm for 1 minute, and then the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0111] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0112] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 10.1 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 31%.
[0113] Example 22 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the specific surface area of porous silica is 159.5 m 2 / g. This embodiment is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW06N5) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0114] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0115] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 159.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 68%.
[0116] Example 23 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the porous silica is preheated to 100° C. The other steps are the same as those in Example 1. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0117] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0118] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0119] Example 24 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the porous silica is preheated to 150° C. The other steps are the same as those in Example 1. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0120] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0121] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0122] Example 25 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the difference is that the porous silica is preheated to 200° C. The other steps are the same as those in Example 1. This example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0123] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0124] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0125] Example 26 Preparation of a Resin-Containing Silica Composition Compared with Example 1, the difference is that 13.05% of dense silica is added based on the total weight of the composition. The other steps are the same as those in Example 1. This example is prepared according to the following method: Porous silica (a product from Sanshiki, model number YYW0605) and dense silica (a product from Sanshiki, model number EQK0605) were mixed and heated to 60°C for 1 minute, that is, the silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form.
[0126] in: Based on the total weight of the composition, the weight proportion of porous silica is 52.17%, the weight proportion of resin is 34.78%, and the weight proportion of dense silica is 13.05%.
[0127] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0128] Based on the BJH method, the specific surface area of dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size of the dense silica was 0.6 μm.
[0129] Comparative Example 1 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the weight of the porous silica accounts for 25% of the total weight of the composition. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0130] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0131] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0132] Comparative Example 2 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the weight of the porous silica accounts for 75% of the total weight of the composition. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYW0605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0133] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0134] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0135] Comparative Example 3 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the average pore size of the porous silica is 4 nm. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWW605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0136] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0137] Based on the BJH method, the average pore size of porous silica is 4 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0138] Comparative Example 4 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the average pore size of the porous silica is 109 nm. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWX605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0139] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0140] Based on the BJH method, the average pore size of porous silica is 109 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 41%.
[0141] Comparative Example 5 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the porosity of the porous silica is 28%. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWY605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0142] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0143] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 28%.
[0144] Comparative Example 6 Preparation of a Silicon Dioxide Composition Containing Resin Compared with Example 1, the only difference is that the porosity of the porous silica is 73%. The other steps are the same as those in Example 1. This comparative example is prepared according to the following steps: The porous silica (a product from Sanshiki, model number YYWZ605) was heated to 60°C and kept warm for 1 minute, that is, the porous silica was preheated to 60°C, and then epoxy resin was added and stirred and mixed at a speed of 1500 rpm for 1 hour to obtain a resin-containing silica composition. Then, the composition was cured at 200°C for 60 minutes to form a shape.
[0145] in: Based on the total weight of the composition, the weight proportion of the porous silica is 60%, and the weight proportion of the resin is 40%.
[0146] Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of the porous silica was 0.6 μm; and the porosity of the porous silica was 73%.
[0147] Performance Characterization The raw material parameters in the examples and comparative examples are shown in Table 1. The relative modulus and thermal expansion coefficient of the cured silicon dioxide composition products obtained in the examples and comparative examples were tested, and the results are shown in Table 1.
[0148] In Table 1, comparative example 2 cannot be formed, so the relative modulus and thermal expansion coefficient data cannot be measured. The modulus is used as a rigidity index of the product and is tested by dynamic thermal mechanical analysis (DMA). The testing equipment is TA dynamic thermal mechanical analyzer Q800, using the three-point bending method, heating from room temperature to 280°C, and testing the 175°C modulus (Mpa). The relative modulus of Example 1 is 1, and the relative modulus of other test samples is the ratio of the 175°C modulus of each test sample to the 175°C modulus of Example 1; the thermal expansion coefficient test uses a thermal mechanical analysis device (purchased from TA Company, USA, model TMA450), and thermal mechanical analysis is performed under the conditions of a preload force of 0.02N, a temperature rise range of 25°C to 260°C, and a heating rate of 10°C / min to obtain the thermal expansion coefficient of the product in the range of 25°C to 120°C.
[0149] In Table 1, the weight ratio is based on the total weight of the porous silica and the resin, and the pore size is the average pore size of the porous silica.
[0150] Table 1 Data Analysis: (1) The present invention forms a substrate material with porous silica and resin, so that the resin passes through the pore structure of the porous silica and penetrates the inside and outside of the porous silica, and the weight of the porous silica accounts for 30% to 70% of the total weight of the composition, thereby obtaining a substrate material with a large silica filling amount, which has excellent rigidity and can avoid warping problems when preparing a coreless substrate.
[0151] The present invention forms a substrate material with porous silica and resin, and its excellent performance is mainly due to the following reasons: First, the resin is made to penetrate the inside and outside of the porous silica through the pore structure of the porous silica, so that the resin is coherent in the composition, and the rigidity and impact resistance of the packaging material are enhanced; second, the resin is made to penetrate the inside and outside of the porous silica through the pore structure of the porous silica, and the porous structure is used to limit the expansion of the resin in the hole, and the warping problem is alleviated; third, based on the improvement of the first and second points above, the composition of the present invention can add 30~70% of porous silica by weight, and avoid the warping problem caused by the decrease in rigidity, so that the composition of the present invention is presented with a large amount of porous silica added, and because the thermal expansion coefficient of the silica material itself is low, the composition of the present invention has a lower thermal expansion coefficient. Combining the above reasons, the resin-containing silica composition of the present invention has a low thermal expansion coefficient, and has high rigidity, so that the composition can remain non-warping when forming a coreless substrate.
[0152] The above-mentioned effect of allowing the resin to pass through the porous silica through the pore structure of the porous silica is not only related to the weight ratio of the porous silica, but also related to the pore size range of the porous silica. It can be seen from the comparative analysis of Example 1 and Example 5 to Example 13 and Comparative Example 3 to Comparative Example 4 that, as preferably, the average number of the pore size of porous silica is 5 to 100nm, and further preferably, the average number of the pore size of porous silica is 16 to 60nm. Specifically, as shown in Example 1 and Example 6 to 10, when the average number of the pore size of porous silica is in the range of 16 to 60nm, the modulus of the composition can be made higher, so that the rigidity is maintained at a higher level.
[0153] Furthermore, based on the characterization data of the present invention, as a preferred embodiment of the composition of the present invention, the cumulative 50% particle size of the porous silica on a volume basis is 0.3~2μm. Specifically, the cumulative 50% particle size of the porous silica on a volume basis in Examples 1, 19 and 20 is 0.6μm, 0.2μm and 3.0μm, respectively, that is, when the D50 particle size of the porous silica is compared as a single variable, when D50 is 0.2μm and 3.0μm, respectively, the rigidity of the product is reduced to varying degrees. In combination with other embodiments, it can be seen that when the cumulative 50% particle size of the porous silica on a volume basis is within the range of 0.3~2μm, the rigidity of the product is better. The reason is that when the D50 particle size is less than 0.3 μm, the particles are easy to agglomerate, and it is difficult for the resin to evenly penetrate the pore structure of the porous silica, resulting in an overall uneven product, which in turn causes a decrease in rigidity; when the D50 particle size is greater than 2 μm, it is difficult for the resin to completely fill the pore structure, which will cause the problem of discontinuity of the resin in the pores, thereby causing the product to have poor local toughness and a decrease in rigidity.
[0154] Further, based on the characterization data of the present invention, as the preferred composition of the present invention, the porosity of porous silica is preferably 30~70%. By comparative analysis of Comparative Examples 5, Comparative Examples 6 and Example 1, it can be seen that when the pore size of porous silica is guaranteed to be within a certain range, the porosity of porous silica is made to be 30~70%, the continuity of the resin in the composition can be improved, and then the rigidity of the composition can be improved. And the pore size of porous silica may be the critical point of rigidity improvement, and after a certain critical pore size, the resin can enter the pores of the particles, and at this time, the porosity is preferably 30~70% to improve the rigidity of the molded composition.
[0155] Furthermore, based on the characterization data of the present invention, as a preferred embodiment of the composition of the present invention, the specific surface area of the porous silica is 15 to 150 m 2 / g. The specific surface area will affect the dispersibility of the porous silica powder, so that the specific surface area of the porous silica is 15~150m 2 / g, the dispersibility of the porous silica can be improved, thereby improving the effect of the resin penetrating the inside and outside of the porous silica through the pore structure of the porous silica, which is specifically reflected in the decrease in the rigidity of the molded products of Examples 21 to 22.
[0156] (2) From the comparative analysis of Example 1 and Comparative Examples 1 and 2, it can be seen that the percentage of porous silica in the total weight of the composition of Comparative Examples 1 and 2 is 25% and 75%, respectively. The rigidity of Comparative Example 1 is sharply reduced. Since the sample block of Comparative Example 2 cannot be formed, it is impossible to measure the data. Therefore, in order to effectively avoid the occurrence of warping problems, it is necessary to control the weight ratio of porous silica as the main material of the substrate material to be within the range of 30% to 70%, and at the same time, the resin passes through the pore structure of the porous silica to penetrate the inside and outside of the porous silica to improve the rigidity of the composition.
[0157] In the embodiment of the present invention, a curing agent is added to the curing of cyanate resin, polyphenylene ether resin, and hydrocarbon resin, and the added amount is 1% of the mass of the resin.
[0158] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0159] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A resin-containing silica composition, characterized in that: The composition comprises porous silica and resin, wherein the resin penetrates the inside and outside of the porous silica through the pore structure of the porous silica; based on the total weight of the composition, the weight of the porous silica accounts for 30% to 70%.
2. A resin-containing silica composition according to claim 1, characterized in that: Based on the BJH method, the average pore size of porous silica is 5 to 100 nm.
3. A resin-containing silica composition according to claim 1, characterized in that: Based on the BJH method, the average pore size of porous silica is 16 to 60 nm.
4. A resin-containing silica composition according to claim 1, characterized in that: The volume-based cumulative 50% particle size of the porous silica is 0.3 to 2 μm.
5. A resin-containing silica composition according to claim 1, characterized in that: Based on the BET method, the specific surface area of the porous silica is 15-150 m 2 / g.
6. A resin-containing silica composition according to claim 1 or 5, characterized in that: The resin is selected from one or more of epoxy resin, cyanate resin, polyphenylene ether resin and hydrocarbon resin.
7. A resin-containing silica composition according to claim 1, characterized in that: After curing at 200° C. for 60 minutes, the thermal expansion coefficient of the composition in the range of 25° C. to 120° C. is 5-50 ppm / K.
8. A method for preparing a resin-containing silicon dioxide composition, characterized in that: The following steps are involved: The porous silica and the resin are mixed so that the resin passes through the pore structure of the porous silica and penetrates the inside and outside of the porous silica; based on the total mass of the composition, the weight proportion of the porous silica is 30% to 70%.
9. The preparation method according to claim 8, characterized in that: The mixing comprises the following steps: Preheat the porous silica to no less than 60°C, add the resin and stir at a speed of 1000-3000 rpm.
10. The preparation method according to claim 8, characterized in that: During the mixing, dense silica is also added.
11. The preparation method according to claim 10, characterized in that: The added mass of the dense silica is not higher than 20% of the total mass of the composition.
12. The preparation method according to claim 10, characterized in that: Based on the BET method, the specific surface area of the dense silica is 1.5~15m 2 / g; the volume-based cumulative 50% particle size of dense silica is 0.3~2μm.
13. Use of the silicon dioxide composition according to any one of claims 1 to 7, or the silicon dioxide composition prepared by the preparation method according to any one of claims 8 to 12 in preparing a coreless substrate.
Citation Information
Patent Citations
Underfill adhesive for electronic packaging device, preparation method of underfill adhesive, and electronic packaging device
CN113403014A